Maintaining tricuspid valve competence in double discordance: a challenge for the paediatric cardiologist. Issue 5 (1st November 1998) - Acar, P; Sidi, D; Bonnet, D; Aggoun, Y; Bonhoeffer, P; Kachaner, J
Abstract : Objectives: To establish the prevalence of tricuspid valve abnormalities in children with a double discordant heart (or congenitally corrected transposition of the great arteries); to study the influence of the loading conditions induced by various surgical interventions on the right and left ventricle in patients with double discordance and an abnormal tricuspid valve; and to propose a rational surgical approach. Methods: Case notes were reviewed of 141 consecutive patients admitted in the first year of life with various types of double discordance (intact ventricular septum (group 1), ventricular septal defect (group 2), ventricular septal defect and pulmonary obstruction (group 3)). A study group of 62 patients with an abnormal tricuspid valve was selected by cross sectional echocardiography. These were followed up through palliative and open heart procedures with grading of tricuspid regurgitation. Results: Tricuspid valve abnormalities were more common in groups 1 and 2 (60% and 56%) than in group 3 (31%). Preoperative tricuspid regurgitation was more common in group 2 (90%) than in groups 1 and 3 (38% and 36%). Ten patients in groups 1 and 2 died in the neonatal period with severe tricuspid regurgitation, associated with coarctation of the aorta in 60%. Eight patients in group 1 had no surgery and are doing well, with a competent tricuspid valve. Palliative procedures were undertaken in 28 patients: 14 had pulmonary artery banding, which resulted in a decrease in tricuspid regurgitation, 12 in group 2 by reducing the pulmonary blood flow and two in group 1 by changing the septal geometry; 14 in group 3 had an aortopulmonary shunt, which induced tricuspid regurgitation in two. Twenty patients are still alive after palliation, with stable tricuspid valve function. Repair of the tricuspid valve was unsuccessful in the three patients who underwent conventional surgery, leaving the right ventricle facing the systemic circulation. In two patients with a competent but abnormal tricuspid valve, conventional surgery induced severe tricuspid regurgitation. Of the 15 patients who underwent conventional surgery, only 10 survived (mortality 33%): eight with a tricuspid valve prosthesis and two with severe residual tricuspid regurgitation. However, tricuspid regurgitation decreased after anatomical correction (nine patients), restoring a systemic left ventricle and a subpulmonary right ventricle, even when the tricuspid valve was not repaired (five patients). Eight patients are doing well after anatomical correction (mortality 11%). Conclusions: Tricuspid valve function in double discordance with an abnormal tricuspid valve depends on the loading conditions of both ventricles and on the septal geometry. Interventions that increase right ventricular volume or decrease left ventricular pressure are likely to induce tricuspid regurgitation, while those that decrease right ventricular volume or increase left ventricular pressure are likely to improve tricuspid valve function. Repair of the tricuspid valve always failed when the right ventricle was left in a systemic position and always succeeded when the right ventricle was placed in a subpulmonary position. These results should be taken in to account when dealing with patients with double discordance and an abnormal tricuspid valve.